Bluetooth profiles : the definitive guide. - Gratton, Dean A., ....- (New Jersey : Prentice Hall, 2003)
Samenvatting:This book is aimed at the Bluetooth community that is currentlydeveloping applications on top of the Bluetooth Core. This book detailsthe usage scenarios for Bluetooth, known as Profiles, essentiallydefining the end-user applications and their interoperabilityrequirements.
Keywords: Draadloze computernetwerken; Mobiele telefonie; Protocollen